Surface Microprocessing AISI-O1 by Pulsed Nd: YAG Laser - Guo, Kelvii Wei (Journal of Coating Science and Technology, 2022)
Due to tedious and time-consuming work put into the conventional mold/die microprocessing (about 37% of the total time of the entire mold/die production). Therefore, to improve or enhance the quality of mold/dies at the final step with a less number of trained and skilled operators or decrease the processing time to cut the overall cost dramatically, AISI-O1 cold work steel was micro-processed by Pulsed Nd: YAG laser. The influence of laser processing parameters on the evolution of the correlated surface morphology was investigated by a 3D profilometer, scanning electron microscopy (SEM), and optical microscopy (OM). The results show that when AISI-O1 specimens were irradiated with various parameters, the morphology of AISI-O1 cold work steel was changed correspondingly. It also demonstrates that the different kinds of micro-processed surface morphology could be established successfully to satisfy the later practical requirements for a given laser. Meanwhile, the effect of laser processing parameters on the relevant temperature was described, and the laser microprocessing temperature field was also proposed. It reveals that the influence of laser pulse feed rate was more prominent than that of other parameters on the relevant micro-processed surface morphology.